Autonomy or Security? Core Value Trade-Offs and Spillovers in Servicescapes for Vulnerable Customers - Sandberg Birgitta; Hurmerinta Leila; Leino Henna M; Menzfeld Mira (Sage, 2022)
This study deepens knowledge on the implementation of core values in servicescapes by analyzing how core value trade-offs and spillovers occur within servicescapes and how vulnerable stakeholders cope with them. We use an explorative approach and draw on rich data collected in two nursing homes. Our study demonstrates how the autonomy-security trade-offs originate in different dimensions of the servicescapes. Further analysis reveals how individual customers may conflict with the core values and core purposes of the respective servicescapes. We also contribute to the discussion on customer vulnerability by considering vulnerability in the extended customer entity and by identifying the active coping mechanisms of vulnerable customers. Practitioners can increase the quality of care by identifying and taking into account the core values of both vulnerable primary and secondary customers and by deliberately supporting their coping with core value trade-offs and spillovers.